The immune microenvironment characterisation and dynamics in hormone receptor–positive breast cancer before and after neoadjuvant endocrine therapy - Gizem Oner; Glenn Broeckx; Christophe Van Berckelaer; Karen Zwaenepoel; Sevilay Altintas; Zafer Canturk; Wiebren Tjalma; Zwi Berneman; Marc Peeters; Patrick Pauwels; Peter A. vanDam (Cancer Medicine, 2023)
Abstract Background Oestrogen receptor positive (ER+)/HER‐2 negative breast cancer (BC) is considered to be an immunologically cold tumour compared to triple negative breast cancer. Therefore, the tumour microenvironment (TME) of ER+/HER‐2 negative BC is understudied. The aim of this project is to investigate the TME and the immune response during neoadjuvant endocrine therapy (NET) and to correlate this with the treatment response in a real life setting. Methods Expression of immune checkpoint receptors and immune cells was examined immunohistochemically, pre‐ and post‐NET in a cohort of 56 ER+/HER‐2 negative BC patients. They were treated with tamoxifen (n = 16), an aromatase inhibitor (n = 40) or a combination of an aromatase inhibitor with a PI3K inhibitor (n = 11) for a median duration of 6 months (range 1–32 months). Immunohistochemical staining with monoclonal antibodies for PDL‐1, PD‐1, TIM‐3, LAG‐3, CTLA‐4, CD4, CD68 and FOXP3 were performed. All staining procedures were done according to validated protocols, and scoring was done by a pathologist specialized in breast cancer. Positivity was defined as staining >1% on TILs. Response to NET was evaluated according to tumour size change on imaging and Ki‐67 change. Results The median age was 61.02 (37–90) years. Diameter of tumour size decreased with a mean of 8.1 mm (−16 mm to 45 mm) (p < 0.001) during NET and the value of Ki‐67 value decreased with a median of 9 after NET (p < 0.001). An increase in PD‐L1 expression after NET showed a trend towards significant (p = 0.088) and CD‐4+ T cells significantly increased after NET (p = 0.03). A good response to NET defined as a decrease in tumour size and/or decrease of Ki‐67 was found to be associated with a longer duration of NET, a change of CD4+ T‐cells and a higher number of CD68+ tumour‐associated macrophages before the start of NET. Conclusion The immune microenvironment plays an important role in ER+/HER‐2 negative BC. NET influences the composition and functional state of the infiltrating immune cells. Furthermore, changes in the immune microenvironment are also associated with treatment response.